Ayapan Farming: New Dimension of Income Generation through Medicinal Crop Farming - Roy, Rakesh; Mridha, Ananda (Indian Horticulture, 2022)
Ayapan farming is gaining popularity among the tribal farmers for large scale production in Habibpur of Malda district. Ayapan is botanically identified as Eupatorium triplinerve is having highly medicinal value. Cultivation of this crop by the farmers of this region was due to its high income and less gross expenditure. The farmers engaged in production of this medical plant was having an income â‚¹7.42 lakhs per ha. in 5 years duration from less irrigated land with less expenditure and physical labour. Therefore, similar land with no or very less irrigation facilities can be converted into ayapan plantations for sustainable income as marketing of this product is comparatively easy due to its high demand.